Zinc-catalyzed ester bond cleavage: Chemical degradation of polyethylene terephthalate. (20th January 2019) - Wang, Yuqi; Zhang, Yao; Song, Hongyan; Wang, Yingxiong; Deng, Tiansheng; Hou, Xianglin
Abstract: Polyethylene terephthalate (PET) materials were recycled by physical methods for a long time. Chemical degradation and recycling of PET materials draw more and more attention in recent years. In this work, PET materials were degraded and recycled via selective cleavage of ester bonds using ZnCl2 as catalysts in aqueous solution. Degradation system 70% ZnCl2 /H2 O presented excellent catalytic properties due to the coordination catalysis of Zn 2+ . Monomers terephthalic acid (TPA) was reclaimed at 180 °C for 8 h. The yield of TPA reached up to 98.31%, and the purity of TPA was up to 97.14%. The degradation system ZnCl2 /H2 O solution was recycled and reused for 3 times, and the degradation ratio of PET materials was still up to 100%. In the degradation process, no organic solvent was added. The work provides a green and sustainable strategy to recover high-value-added chemicals (TPA) from waste PET materials in aqueous phase. Graphical abstract: Chemical degradation of polyethylene terephthalate was developed to produce terephthalic acid and ethylene glycol via selective cleavage of ester bonds. Highlights: Chemical degradation of PET material was achieved via selective cleavage of ester bonds. The coordination catalysis of Zn 2+ accelerated the hydrolysis process of ester bonds. High value-added chemicals were recovered from waste PET materials.